Undertaking the act of writing as a situated social practice: going beyond the Linguistic and the textual - Chapetón Castro, Claudia Marcela; Chala, Pedro Antonio (Colombian Applied Linguistics Journal, 2013)
With an interest to go beyond an emphasis on linguistic and textual features that seem to prevail in writing practices, this qualitative action research study looked at EFL argumentative essay writing within a genre-based approach, where writing was understood as a situated social practice. A group of undergraduate students from a B.Ed. program in Modern Languages participated in the study. Data were gathered through semi-structured interviews, questionnaires, class recordings, and students’ artifacts. Findings revealed that participants undertook the writing of argumentative essays by bonding with their audience, establishing personal involvement with their texts, and giving support to their arguments. The study suggests that it is important to encourage students to focus on their sociocultural and personal context so that EFL writing can be approached in a more purposeful and meaningful way.